1999
DOI: 10.5059/yukigoseikyokaishi.57.1016
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of an Endothelin Receptor Antagonist.

Abstract: Two distinct synthetic approaches to the biologically active and structurally unique endothelin antagonist J-104132 (1) have been developed Each synthesis involves a highly selective intramolecular cyclization of a late stage intermediate (bottom to top vs top to bottom) produced from a common early intermediate. Both routes initially yielded multi-gram quantities of the desired product, with the former ultimately developed to pilot scale readiness.Several novel reactions have been developed throughout the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Earlier work on the synthesis of 1a showed that both are viable approaches. 6,7) We have recently disclosed a practical asymmetric synthesis of 1b utilizing the "bottom to top" approach A. 8) We have also disclosed an alternative asymmetric synthesis of 1b starting from amino substituted pyridine utilizing the "top to bottom" approach B.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work on the synthesis of 1a showed that both are viable approaches. 6,7) We have recently disclosed a practical asymmetric synthesis of 1b utilizing the "bottom to top" approach A. 8) We have also disclosed an alternative asymmetric synthesis of 1b starting from amino substituted pyridine utilizing the "top to bottom" approach B.…”
Section: )mentioning
confidence: 99%
“…With the intermediate 21 in hand, methoxycarbonylation of 21 15) was accomplished with CO (1 kg/cm 2 ) in methanol in the presence of NaHCO 3 and a catalytic amount of Pd(OAc) 2 and 1,1Ј-bis(diphenylphosphino)ferrocene (DPPF) in 97% yield. From the readily accessible 4-bromo-3-hydroxymethylanisole, 6,7) the bottom aryl bromide 23 was prepared by introduction of the PMB ( p-methoxybenzyl) protecting group to the hydroxymethyl group under standard conditions. Chemoselective addition of aryllithium from 23 to the methyl ester of 22 at low temperature afforded ketone 24 in 88% yield (Chart 4).…”
Section: Asymmetric Synthesis Of a Selective Endothelin A Receptor Anmentioning
confidence: 99%